Santa Cruz Skills Commons revitalizing Santa Cruz as a construction district - Lasaleta, Lorenzo Jarell R. (College of Architecture, University of the Philippines Diliman, 2020)
Santa Cruz was once a commercial powerhouse in Manila, but the district has not been able to keep up with the outward expansion of the capital. What is left of the district are half empty shells of dilapidated post was buildings wildly in contrast with the prolific life on the streets from pedestrians, street vendors, and ground level shops. Given the current political climate where urban space is highly contested where there is question as to who gets to occupy what and who gets to occupy at all, and the environmental climate in which the construction industry is a major pollutant, to regard these buildings only as half empty shells of the past is the potential to reconnect the past, the present and the future. To understand the extent of Santa Cruz's decay and flesh out the best way to revitalization, an analysis of the district was conducted through the decrepit buildings. A set of criteria was created in determining decaying buildings then the streets of Lower Santa Cruz were surveyed, and the identified buildings were classified. From the mapping of the buildings, areas of high occupancy despite decay were determined and Arranque was selected as the key area development. The revitalization of the district will focus on empowering the rich construction history of the district through educating the labor force, celebrating street culture of vendors, and honoring built heritage. The resulting development shows that an understanding of the underlying history, context, and nuances of the site are vital in revitalization.